Analysis of topo-morphological influence of vineyards in the design of wireless sensor networks for smart viticultural management. (2015) - Gil, Guillermo; Goyeneche, Marcos; Azpilicueta, Leire; Astrain, José Javier; Villadangos, Jesús; Falcone, Francisco
In this work, the influence of topology as well as morphology in the integration of wireless sensor networks (WSNs) in vineyards is analysed. The impact on wireless propagation is analysed by means of an in-house 3D ray launching code, to emulate the realistic operation framework of the scenario. To gain insight into the effects on radiopropagation, a simplified vine model has been developed, considering the material parameters and simplified geometry embedded in the simulation scenario. Measurement results from deployed IEEE 802.15.4 sensors in a real vineyard are presented, in terms of received power levels as well as of packet transmission performance of the wireless nodes. The knowledge of the topological influence can aid in the deployment of the optimal WSN in terms of capacity as well as energy consumption, making the use of these systems attractive in viticulture management processes.